Rapid solidification and liquid-phase separation of undercooled CoCrCuFexNi high-entropy alloys. (May 2016) - Liu, N.; Wu, P.H.; Zhou, P.J.; Peng, Z.; Wang, X.J.; Lu, Y.P.
Abstract: Fluxing and cyclic superheating technique was used to investigate the rapid solidification behavior of CoCrCuFex Ni (x = 1.0, 1.5, 2.0, molar concentration) high-entropy alloys in this study. The microstructures of CoCrCuFex Ni (x = 1.0, 1.5, 2.0) high-entropy alloys solidified at different undercoolings (ΔT) were investigated. Liquid-phase separation leading to Cu-rich and Cu-depleted regions, were obtained in the solidified microstructure from highly undercooled melt. This occurs when the melt undercooling exceeds a critical undercooling (ΔTcrit ) of 160 K for CoCrCuFeNi, 190 K for CoCrCuFe1.5 Ni and 293 K for CoCrCuFe2 Ni alloy. However, typical dendrites and interdendritic regions were observed in rapid-solidified CoCrCuFex Ni alloys prepared from melts with a small undercooling (ΔT < ΔTcrit ). Conversely, a large amount of Cu-rich spheres and even egg-type structures were observed in alloys solidified from melts with large degree of undercooling, ΔT in excess of the critical value, ΔTcrit . A large amount of Cu-rich nano-phases were found in the matrix, possibly, due to the precipitation of Cu-rich phase from the supersaturated solid solution obtained during solidification. The positive enthalpies of mixing between Cu and the other elements in the multi-component alloys resulted in the occurrence of liquid-phase separation prior to the liquid–solid transformation starts. The sluggish diffusion effect of high-entropy alloys and rapid solidification play an important part in the precipitation of nanophase during the solid-state transformation in the Cu-based matrix. Similar to other immiscible alloys, liquid-phase separation occurred when a critical undercooling was exceeded. Differently, nanophases were found in the microstructures of multi-component CoCrCuFex Ni (x = 1.0, 1.5, 2.0) alloys. Highlights: Rapid solidification of undercooled multi-component CoCrCuFexNi high-entropy alloys was investigated for the first time. Liquid-phase separation occurs when a critical undercooling (ΔT crit). With the increase of undercooling, the liquid-phase separation becomes more evident. The presence of supersaturated solid solution and Cu-rich nanosized phases in CoCrCuFeNi high-entropy alloy is synergistic effects of high entropy of mixing and sluggish atomic diffusion in solid state.